Parallel semantic processing in reading revisited: effects of translation equivalents in bilingual readers. - Snell, Joshua; Declerck, Mathieu; Grainger, Jonathan (Language, Cognition & Neuroscience, 2018)
Previous research has failed to establish semantic parafoveal-on-foveal effects during reading. As an explanation, we theorise that sentence reading engages a sentence-level representation that prevents semantic parafoveal-foveal integration. Putting this account to the test, we examined parafoveal-foveal influences both in- and outside a sentence reading setting. Optimising chances of establishing parafoveal-on-foveal effects, we used translation-equivalent word pairs with French-English bilingual participants. Experiment 1 provided no evidence for semantic parafoveal-on-foveal integration during sentence reading, but some evidence that semantic information had been extracted in parallel from multiple words. Experiments 2 and 3 employed a flanker paradigm in which participants semantically categorised English foveal target words, while these were flanked by the French translation or an unrelated French word (stimulus on-time 170 ms). Performance was drastically better with translation flankers, suggesting that readers can integrate semantic information across multiple words when the task does not require a strict separation of higher-order information.